UPAYA GURU DALAM MENINGKATKAN PERILAKU KEAGAMAAN SANTRI MELALUI METODE KETELADANAN - Erna Nurpitasari; Muhammad Heriyudanta; Marjanji Marjanji (TA'LIM : Jurnal Studi Pendidikan Islam, 2021)
The declining awareness of the Santri of the Santri of Al Ikhlas Village Bringin will be a religious behavior due to lack of parental attention to the religious behavior of santri, the social environment is less supportive, and social media. The number of santri who behave is not good, speaks less well before his friends and fellow friends, perform prayer in congregation is not routine and lazy to read the Qur'an. This study aims to determine the efforts of teachers in Menin: Explay religious knowledge, students' santri attitudes, and santri's worship skills through the Method of Mittens in Al Ikhlas, to find out the obstacles facing the teacher in increasing the religious behavior of the santri in Al Ikhlas TPA and to find out the implications of the example method For increasing the religious behavior of the santri in the land of Al Ikhlas. To answer the above research, researchers use a qualitative approach and type of case study research. Data collection techniques use interviews, observation, and documentation. The data analysis technique uses data reduction, data presentation, and verification taking. Based on the results of the study, it shows conclusions is its efforts in the form of giving a good example in being and speaking, giving guidance in reading the Qur'an or Iqro ', getting used to and inviting santri to pray in congregation. As for the constraints, the influence of the environment that is less supportive, the lack of cooperation between teachers and parents, santri is lazy in reading the Qur'an, and the number of santri who behave is not good. And the implications, namely santri little by little have shown changes in behaving like santri have used to speaking and being polite, the santri diligently deposited the reading of the Qur'an, and the santri began to get used to praying in congregation.